Digital Value-Based Pricing Strategy in Tourism Marketing: A Systematic Literature Review Approach - Rabiul Awal, Rais Iqbal; Rahayu, Agus; Hendrayati, Heny; Heryana, Nono; Yudha Rahman, Shandika; Deny, Muhammad; Lestari, Fitri (Dinasti Publisher, 2025)
This research is motivated by the importance of digital value-based pricing strategies in optimizing the competitiveness of tourism destinations in the digital era. This background highlights the need for an approach that integrates technology and a deep understanding of consumer behavior to create perceived value for tourists. The study aims to identify effective, relevant, and competitive pricing strategies in digital value-based tourism marketing. The method used is the Systematic Literature Review (SLR) with the PRISMA framework, combined with bibliometric analysis to ensure the validity and relevance of the research data. The results of the study indicate that digital value-based pricing strategies, which utilize data analytics and personalization, can increase tourists' perceived value, satisfaction, and loyalty while driving the economic sustainability of tourist destinations. The conclusion of this study confirms that digital value-based strategies are not only relevant but also able to create satisfying tourism experiences, support marketing innovation, and have the potential to become a long-term trend in the tourism industry.